Economic policies in small open economies: prospects for the Caribbean - Worrell, Delisle (Commonwealth Secretariat LondonUK, 1992)
Argues that the economic adjustment strategies adopted by many Caribbean economies in the 1980s were inappropriate in trying to restore external balance and raise economic output. Highlights the economic adjustment strategies of Barbados, the Dominican Republic, Guyana, Jamaica and Trinidad and Tobago.